Effect of the Culturo-Techno-Contextual Approach on BiologyRetention Among Secondary School Students in NsukkaEducation Zone - Oshabaonuh, Onyinyechi Maureen; Okereke, Innocent Ebere; Okigbo, Ebele Chinelo (Institut Teknologi Pendidikan Indonesia, 2025)
The study determined the effect of Culturo-Techno-Contextual Approach (CTCA) on Biology retention among secondary school students in Nsukka Education Zone of Enugu State, Nigeria. The study was guided by two research questions and three null hypotheses using quasi-experimental research design. Population of study consisted of 2,870 senior secondary school year two (SS2) students offering Biology in the government-owned co-educational secondary schools in the zone. Eighty-one (81) SS2 students were sampled from two out of 41 co-educational schools in the zone using multistage sampling procedure. The instrument for data collection was Biology Achievement Test (BAT). The instrument was validated by three experts from Faculty of Education in Nnamdi Azikiwe University, Awka. Kudder-Richardson Formula 20 was used to establish a reliability coefficient of 0.87 for BAT. The experimental group was taught using CTCA while the control group was taught using conventional lecture method. Mean and standard deviation were used to answer the research questions, while Analysis of covariance was used to test the null hypotheses at 0.05 alpha level. The findings revealed among others that CTCA significantly enhanced the retention of students in Biology more than conventional lecture method. Also, CTCA is a gender friendly teaching approach that could be used to enhance the retention of secondary school male and female students in Biology equally. It was concluded that CTCA is an effective teaching approach that could be adopted as an alternative instructional approach for teaching of Biology in Nsukka Education Zone. Based on the findings of the study, it was recommended that teachers should be trained on how to use CTCA to improve retention of students in Biology through seminars, workshops and conferences. Also, secondary school Biology teachers should be encouraged by school administrators to adopt the use of CTCA for Biology instructions.